An efficient routing technique for mesh-of-tree-based NoC and its performance comparison. (1st January 2012) - Manna, K.; Chattopadhaya, S.; Sengupta, I.
This paper presents a new dimension ordered routing (DOR) algorithm for mesh-of-tree (MoT)-based network-on-chip (NoC) designs. A simple addressing scheme has been used in this new algorithm. The addressing scheme enables us to reduce the minimum flit-size for a 4 ´ 4 MoT to 16 bits, compared to 32 bits in the previously reported works. The algorithm has been proved to be deadlock, live-lock and starvation free. It also ensures shortest-path routing for the packets. It results in significant saving in the energy consumed by the network. It allows us to vary router complexity flexibly while planning the MoT-based NoC for application specific system-on-chip (SoC) synthesis. Performance and cost metric comparison with other topologies shows the proposed MoT to be better than many of them.